Assessment of the Nutritional Status of Hepatocellular Carcinoma Patients: Evaluating methods and correlation with disease severity— cross-sectional study - Shimaa Ahmed Gamal; Wesam Saber Morad; Gasser El-Azab; Sania Ali Yehia (Egyptian Liver Journal)
Abstract Background Hepatocellular carcinoma (HCC) patients are vulnerable to malnutrition. Despite its importance in enhancing clinical outcomes, management, and prognosis of HCC patients, few studies assessed their nutritional status. Our study aimed to evaluate the nutritional status of HCC patients using various nutritional assessment methods and their correlation with disease severity. Patients and methods This is a cross-sectional hospital-based study of 200 HCC patients who visited outpatient clinics at the National Liver Institute. Methods used for assessment of their nutritional status included body mass index (BMI), mid-arm circumference (MAC), mid muscle arm circumference (MMAC), calf circumference (CC), hand grip strength (HGS), adductor pollicis muscle (APM) thickness, subjective global assessment (SGA), and mini-nutritional assessment (MNA) questionnaire. Results The mean age of study participants was 61.51 ± 8.68 years. There was a wide variation in the diagnosis of malnutrition in HCC patients using different nutritional assessment methods. There was substantial agreement between MAC and MNA with SGA. There was a negative correlation between child class and MAC, MMAC, and MNA scores. There was a negative correlation between BCLC and MNA scores. SGA was positively correlated with both child class and BCLC staging. Conclusions There was a great variation in the prevalence of malnutrition in HCC patients using different nutritional assessment methods. MAC and MNA scores showed a substantial agreement with SGA. SGA, MNA, MAC, and MMAC correlated with disease severity. Assessing the nutritional status is necessary to improve patients’ clinical outcomes.